Kesesuaian Akuntansi Zakat, Infak dan Sedekah Dengan PSAK 109 BAZNAS Kabupaten Tulungagung - Lantip Susilowati; Fatimatul Khofifa (JAS (Jurnal Akuntansi Syariah), 2020)
The potential for receiving zakat, infaq and alms funds in Tulungagung is growing rapidly. This shows that the level of trust in the management of zakat, infaq and alms funds is quite high. This study aims to examine the suitability of the application of PSAK 109 in the National Zakat Agency Tulungagung Regency. The method used in this research is a descriptive qualitative approach. Sources of data used are interviews, observation and documentation. The results showed that the accounting treatment at National Zakat Agency Tulungagung Regency included the receipt and expenditure of zakat, infaq and alms which was recognized as the amount of cash received and disbursed, presented and disclosed on the financial statements. Recognition and measurement of accounting treatment at National Zakat Agency Tulungagung Regency are in accordance with PSAK 109, while its presentation and disclosure are not fully in accordance with PSAK 109. The main obstacle faced is the limited qualified human resources and still uses a manual system in making financial reports.